Surface-treated aluminum nitride powder
Patent Information
- Application Number
- JP2025060726
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-14
AI Technical Summary
【0019】 本発明により、高い耐水性を有し、かつシリコーン樹脂と親和性が高く、分散性に優れた表面処理窒化アルミニウム粉末を得ることができる。前記表面処理窒化アルミニウム粉末をシリコーン樹脂に充填することで、成形·加工に適しており、且つ、放熱部材、特には半導体製品として高い信頼性を有するシリコーン樹脂組成物を得ることが可能となる。
Smart Images

Figure 2026167247000001 
Figure 2026167247000002 
Figure 2026167247000003
Abstract
Description
[Technical Field]
[0001] This invention relates to a novel surface-treated aluminum nitride powder. [Background technology]
[0002] In recent years, with the increasing performance of electronic devices and components, the miniaturization and high integration of electronic devices have progressed even further. As a result, the heat density has increased, and thermal management has become an urgent issue. Various heat dissipation materials are used to dissipate the heat generated from semiconductor chips, which are the heat source, to heat sinks, housings, etc. Examples of such heat dissipation materials include thermal grease, thermal conductive adhesives, thermal sheets, and semiconductor encapsulants. One example of such a material is a silicone resin composition in which a heat dissipation filler is filled into a silicone resin. Examples of the heat dissipation filler include aluminum oxide (alumina), aluminum nitride, and boron nitride. Among these, aluminum nitride is attracting attention as a heat dissipation filler because it has high thermal conductivity and electrical insulation properties.
[0003] These compositions are often used after being molded and processed into the desired shape, and then polymerized and cured as needed. In this process, the better the filler's dispersibility in the resin and the higher the fluidity of the silicone resin composition with the filler, the more suitable it is for molding and processing. A simple method for improving the dispersibility of the filler in the resin is to perform surface treatment according to the type of resin.
[0004] Furthermore, aluminum nitride powder undergoes hydrolysis upon contact with moisture, transforming into aluminum hydroxide along with the generation of ammonia. The formation of aluminum hydroxide, which has low thermal conductivity, undermines the inherent advantages of aluminum nitride. In addition, the generated ammonia can contribute to corrosion of metal wiring inside devices and to ion migration. Especially in semiconductor products, where high reliability is required, the aluminum nitride powder used must have high water resistance to prevent hydrolysis over long periods. One method for evaluating such water resistance is accelerated testing under high temperature and high humidity conditions, where the filler powder is immersed in water at high temperatures of 85°C or 120°C. If hydrolysis hardly progresses in this accelerated test, it can be said that the powder has high water resistance.
[0005] As described above, aluminum nitride powder, which offers both high dispersibility in silicone resins and water resistance, is important for heat dissipation in electronic devices.
[0006] For example, Patent Document 1 describes how water resistance is obtained by heating aluminum nitride powder, whose surface is coated with an organosilicone compound, at a temperature of 300°C to less than 1000°C to form an SiO2 coating on the particle surface. However, SiO2-coated aluminum nitride particles do not have sufficient water resistance at high temperatures. In addition, surface treatments tailored to the type of resin are unsuitable.
[0007] Furthermore, Patent Document 2 shows that hydrophobic aluminum nitride powder, obtained by surface-treating aluminum nitride powder with a silane compound, has improved water resistance. This hydrophobic aluminum nitride powder exhibits low hydrolysis and water resistance even when kept in water at room temperature for 24 hours. However, hydrolysis proceeds immediately when immersed in water under high-temperature conditions such as 85°C or 120°C. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2020-193141
Patent Document 2
Summary of the Invention
Problem to be Solved by the Invention
[0009] The present invention has been made in view of the circumstances as described above, and an object of the present invention is to provide a surface-treated aluminum nitride powder that has high water resistance, high affinity with silicone resins, and excellent dispersibility.
Means for Solving the Problem
[0010] As a result of extensive and diligent studies to achieve the above object, the present inventors have found that all the aforementioned problems can be solved by subjecting aluminum nitride powder to surface treatment with two types of silane compounds: a specific amount of a crosslinkable silane compound having a functional group capable of bonding to hydroxyl groups on the surface of aluminum nitride particles, and an affinity silane compound having a functional group with high affinity for silicone resins, and have completed the present invention.
[0011] That is, the present invention is a surface-treated aluminum nitride powder that is surface-treated with at least two silane compounds, namely a crosslinkable silane compound represented by either of the following general formulas (1) and (2) and an affinity silane compound having an alkyl group, wherein the content of the crosslinkable silane compound is 100 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of the affinity silane compound.
[0012]
Chemical Formula
[0013] (In the aforementioned general formula (1), R 11 to R 16each independently represents any one selected from a hydrocarbon chain, an alkoxy group, a hydroxy group, a halogen atom, and a hydrogen atom, and each Si atom has at least one functional group capable of bonding to a hydroxyl group on the surface of aluminum nitride particles. X represents a single bond or a functional group having 1 to 14 main chain atoms connecting the Si atoms at both terminals.)
[0014]
Chemical Formula
[0015] (In General Formula (2), R 21 ~R 29 each independently represents any one selected from a hydrocarbon chain, an alkoxy group, a hydroxy group, a halogen atom, and a hydrogen atom, and each Si atom has at least one functional group capable of bonding to a hydroxyl group on the surface of aluminum nitride particles. Y represents a functional group having 1 to 14 main chain atoms connecting the Si atoms at both terminals.)
[0016] In a water resistance test in which 1 g of the surface-treated aluminum nitride powder and 50 g of ion-exchanged water are placed in a sealed container and heated at 120°C for 24 hours, the surface-treated aluminum nitride powder preferably has a hydrolysis rate of 10% or less. Further, it is preferable that the cumulative volume 50% particle diameter (D50) measured by a laser diffraction-scattering particle size distribution analyzer using ethanol as a dispersion medium is in the range of 0.1 to 40 μm.
[0017] Further, one embodiment of the present invention is a filler for silicone resins composed of the surface-treated aluminum nitride powder. Furthermore, one embodiment of the present invention is a silicone resin composition containing a silicone resin and the filler, and a heat dissipation member containing the silicone resin composition or a cured product thereof.
[0018] Furthermore, one embodiment of the present invention is a method for producing surface-treated aluminum nitride powder, comprising the step of mixing raw material aluminum nitride powder, the crosslinkable silane compound, and the affinity silane compound, and then heating at 40°C or higher, wherein the amount of the crosslinkable silane compound is 100 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the affinity silane compound. [Effects of the Invention]
[0019] The present invention provides a surface-treated aluminum nitride powder that has high water resistance, high affinity with silicone resin, and excellent dispersibility. By filling a silicone resin with this surface-treated aluminum nitride powder, it becomes possible to obtain a silicone resin composition that is suitable for molding and processing, and has high reliability as a heat dissipation member, and especially as a semiconductor product. [Modes for carrying out the invention]
[0020] The embodiments for carrying out the present invention will be described in detail below.
[0021] [Surface-treated aluminum nitride powder] The surface-treated aluminum nitride powder in this invention is surface-treated with a crosslinkable silane compound and an affinity silane compound. In this invention, the surface-treated aluminum nitride particles have their surfaces densely coated with two types of silane compounds. As a result, hydrolysis is suppressed even in water, and high stability is achieved. Furthermore, the inclusion of an affinity silane compound increases the affinity between the aluminum nitride particles and the silicone resin, resulting in excellent dispersibility in the silicone resin. As shown in Patent Document 2, it is possible to improve the water resistance of aluminum nitride powder to some extent with only an affinity silane compound, but by combining an affinity silane compound and a crosslinkable silane compound as in this invention, water resistance is further improved, and a surface-treated aluminum nitride powder with particularly high reliability can be obtained, exhibiting a low hydrolysis rate even in high-temperature tests (accelerated tests) at 85°C and 120°C.
[0022] The total amount of the two types of silane compounds constituting the surface-treated aluminum nitride powder is not limited, but is preferably 35 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of aluminum nitride. Furthermore, it is preferably 0.02 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 1 part by mass or more, per 100 parts by mass of aluminum nitride. By keeping the amount of silane compounds below the above upper limit, surface treatment can be easily performed without hindering heat conduction between particles. By keeping the amount of silane compounds above the above lower limit, it is easy to improve water resistance.
[0023] The amount of the crosslinkable silane compound is preferably 150 to 250 parts by mass, and more than 100 parts by mass, of the affinity silane compound, with a maximum of 100 parts by mass and a maximum of 300 parts by mass. By being above the lower limit, the spaces between adjacent affinity silane compounds on the aluminum nitride particles can be filled without excess or deficiency, resulting in high water resistance. By being below the upper limit, the effects of both the affinity silane compound and the crosslinkable silane compound can be achieved.
[0024] Surface-treated aluminum nitride powder preferably has a hydrophobicity of 25 or higher, and more preferably 30 or higher. Increasing the hydrophobicity makes it easier to further improve water resistance. The hydrophobicity of surface-treated aluminum nitride powder can be evaluated by its precipitation in a mixed solvent of water and methanol. Specifically, 100cc of methanol aqueous solution is prepared in 200cc beakers at concentrations in 1% by volume increments, 1g of surface-treated powder is added to each aqueous solution, and the solutions in the beakers are stirred with a magnetic stirrer for 5 minutes. The hydrophobicity is defined as the volume percentage of methanol when 50% of the surface-treated aluminum nitride powder is suspended in the solution.
[0025] The specific surface area of the surface-treated aluminum nitride powder of the present invention is not particularly limited, but for example, 0.1 m² 2 / g or more 10m 2 Less than / g, especially 0.2m 2 / g or more 5m2 / g or less may also be used.
[0026] For the surface-treated aluminum nitride powder, the value obtained by dividing the carbon content of the surface-treated aluminum nitride powder by the specific surface area of the surface-treated aluminum nitride powder measured by the nitrogen gas adsorption method is 1.2 to 2.5 mg / m 2 , preferably 1.5 to 2.3 mg / m 2 . This makes it easy to obtain surface-treated aluminum nitride particles that are sufficiently coated with the surface treatment agent and imparted with high water resistance without impairing thermal conductivity. The carbon content means the carbon content per 1 g of the powder, and can be calculated from CO₂ generated by burning the powder at 1350°C. The carbon content of the surface-treated aluminum nitride powder serves as an indicator of the amount of the surface treatment agent bound to the surface of the surface-treated aluminum nitride powder.
[0027] The surface-treated aluminum nitride powder of the present invention preferably has a cumulative volume 50% particle diameter (D50) in the range of 0.1 to 40 μm, more preferably 0.3 to 25 μm, as measured by a laser diffraction-scattering particle size distribution analyzer using ethanol as a dispersion medium. The D50 measurement is performed on a dispersion prepared by adding the surface-treated aluminum nitride powder to ethanol at a concentration of 0.2 mass%, and dispersing the mixture by ultrasonic irradiation of about 200 W for 3 minutes. D50 refers to the particle diameter value at which the cumulative value reaches 50% when the volume frequency of particle diameters is accumulated in the volume distribution of particle diameters obtained by measurement with a laser diffraction-scattering particle size distribution analyzer.
[0028] The shape of the primary particles of the surface-treated aluminum nitride powder in the present invention is not particularly limited, and may be any arbitrary shape such as irregular shape, spherical shape, polyhedral shape, columnar shape, whisker shape, and flat plate shape. Above all, for filler applications, a spherical shape with favorable viscosity characteristics and high thermal conductivity reproducibility is desirable. A smaller particle aspect ratio is preferred. A suitable aspect ratio is 1 to 3. [Crosslinkable silane compound] The crosslinkable silane compound in this invention refers to a silane compound represented by either general formula (1) or (2).
[0029] [ka]
[0030] (In the above general formula (1), R 11 ~R 16 Each of these independently represents one of the following: a hydrocarbon chain, an alkoxy group, a hydroxyl group, a halogen atom, or a hydrogen atom, and each Si atom has at least one functional group capable of bonding to a hydroxyl group on the surface of the aluminum nitride particle. X represents a functional group with a single bond or a main chain with 1 to 14 atoms connecting the Si atoms at both ends.
[0031] [ka]
[0032] (In general formula (2), R 21 ~R 29 Each of the following independently represents a hydrocarbon chain, alkoxy group, hydroxyl group, halogen atom, or hydrogen atom, and each Si atom has at least one functional group capable of bonding to the hydroxyl group on the surface of the aluminum nitride particle. Y represents a functional group with 1 to 14 atoms in the main chain connecting the Si atoms at both ends.
[0033] Such crosslinkable silane compounds have multiple Si atoms within a single molecule, each to which a functional group capable of binding to the hydroxyl groups on the surface of aluminum nitride particles is attached. This allows a two-dimensional network formed by crosslinking via intermolecular siloxane bonds to be immobilized on the surface of the aluminum nitride particles. Therefore, the surface of the aluminum nitride particles can be densely coated with the silane compound, thereby suppressing contact of water molecules with the surface of the aluminum nitride particles and improving the water resistance of the powder.
[0034] General formula (1) represents a silane compound having two Si atoms in one molecule, each having at least one functional group capable of bonding to a hydroxyl group on the surface of aluminum nitride particles, while general formula (2) represents a silane compound having three such Si atoms. 11 ~R 16 and R 21 ~R 29 Specific examples of functional groups that can bond to the hydroxyl groups on the surface of the aluminum nitride particles include hydroxyl groups or functional groups that can be converted to hydroxyl groups. Examples of functional groups that can be converted to hydroxyl groups include alkoxy groups and halogen atoms. Examples of alkoxy groups include methoxy groups, ethoxy groups, and i-propoxy groups. Functional groups other than those that can bond to the hydroxyl groups on the surface of the aluminum nitride particles include hydrogen atoms and hydrocarbon groups having 1 to 5 carbon atoms.
[0035] In general formula (1), R 11 ~R 16 It is not necessary for all of the functional groups to be able to bond to the hydroxyl groups on the surface of aluminum nitride particles, but the more functional groups that can bond to the hydroxyl groups on the surface of aluminum nitride particles there are, the easier it is to construct a denser and larger-area siloxane network. For this reason, it is preferable that the crosslinkable silane compound shown in general formula (1) has four or more functional groups that can bond to the hydroxyl groups on the surface of aluminum nitride particles in one molecule. Similarly, it is preferable that the crosslinkable silane compound shown in general formula (2) has four or more, particularly six or more, functional groups that can bond to the hydroxyl groups on the surface of aluminum nitride particles in one molecule.
[0036] In general formulas (1) and (2), if the chain lengths of X and Y are too long, the distance between crosslinking points becomes large, resulting in a siloxane network with low crosslinking density, which reduces the effect of improving the water resistance of the surface-treated aluminum nitride powder. On the other hand, if the chain lengths of X and Y are too short, aggregation of crosslinkable silane compounds occurs preferentially, which can make it difficult to uniformly coat the aluminum nitride particles. Therefore, it is preferable that X and Y have 1 to 14 atoms connecting the Si atoms at both ends of the molecule (i.e., functional groups with 1 to 14 atoms in the main chain connecting the Si atoms at both ends), and more preferably 2 to 12 (i.e., functional groups with 2 to 12 atoms in the main chain connecting the Si atoms at both ends). Examples of X and Y include straight-chain or side-chain hydrocarbon chains, and may optionally contain bonds with fluorine, boron, nitrogen, oxygen, silicon, phosphorus, and sulfur atoms.
[0037] Specific examples of X include structural formulas A to J shown below. Structural formulas A, C to I may have side chains and may also have unsaturated bonds. The side chains are preferably alkyl chains with fewer than 5 carbon atoms. Having side chains can increase the coverage of the aluminum nitride particle surface, making it easier to improve water resistance. On the other hand, if the side chains are too long, it can cause aggregation of silane compounds.
[0038] [ka]
[0039] Specific examples of Y include the following structural formulas M and N.
[0040] [ka]
[0041] Specific examples of crosslinkable silane compounds represented by the above general formula (1) include 1,2-bis(chlorodimethylsilyl)ethane, bis[2-(chlorodimethylsilyl)ethyl]benzene, 1,3-bis(chlorodimethylsilyl)propane, 1,6-bis(chlorodimethylsilyl)hexane, 1,8-bis(chlorodimethylsilyl)octane, bis[(3-chlorodimethylsilyl)propyl]ether, bis(dichlorosilyl)methane, 4,4'-bis(dimethylethoxysilyl)biphenyl, bis(ethoxydimethylsilyl)methane, and 1,4-bis(hydrox 1,4-Bis(methyldichlorosilyl)butane, 1,2-Bis(methyldichlorosilyl)ethane, 1,2-Bis(methyldiethoxysilyl)ethane, 1,2-Bis(methyldiethoxysilyl)ethylene, Bis(methyldiethoxysilylpropyl)amine, 1,2-Bis(methyldifluorosilyl)ethane, 1,2-Bis(methyldimethoxysilyl)ethane, Bis(methyldimethoxysilyl)methane, Bis(methyldimethoxysilyl)propyl)-N-methylamine, Bis(trichlorosilyl)acetylene, 1,10-Bis( (Lichlorosilyl)decane, 1,2-bis(trichlorosilyl)ethane, bis(trichlorosilylethyl)benzene, 1,6-bis(trichlorosilyl)hexane, bis(trichlorosilyl)methane, 1,1-bis(trichlorosilylmethyl)ethylene, 1,8-bis(trichlorosilyl)octane, 1,3-bis(trichlorosilyl)propane, 1,4-bis(triethoxysilyl)benzene, 4,4'-bis(triethoxysilyl)biphenyl, 1,2-bis(triethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethylene, bis( Riethoxysilyl)methane, 1,8-bis(triethoxysilyl)octane, bis(3-triethoxysilylpropyl)amine, bis[3-(triethoxysilyl)propyl]disulfide, 1,2-bis(trimethoxysilyl)decane, 1,6-bis(trimethoxysilyl)-2,5-dimethylhexane, 1,2-bis(trimethoxysilyl)ethane, bis(trimethoxysilylethyl)benzene, 1,6-bis(trimethoxysilyl)hexane, bis(trimethoxysilylmethyl)benzene, 1,1-bis(trimethoxyylmethyl)ethylene, 1,8-Bis(trimethoxysilyl)octane, bis(3-trimethoxysilylpropyl)amine, 1,3-bis(trimethoxysilylpropyl)benzene, N,N'-bis[(3-trimethoxysilyl)propyl]ethylenediamine, bis(3-trimethoxysilylpropyl)-N-methylamine, 1,7-dichlorooctamethyltetrasiloxane, 1,3-dichlorotetramethyldisiloxane, 1,5-diethoxyhexamethyltrisiloxane, 1,2-diethoxytetra Examples include methyldisilane, 1,2-dihydroxytetramethyldisiloxane, 1,2-dimethoxytetramethyldisilane, 1,3-dimethyltetramethoxydisiloxane, 1,3-divinyltetraethoxydisiloxane, hexachlorodisiloxane, 1,1,3,3-tetraethoxy-1,3-dimethyldisiloxane, 1,1,3,3-tetraisopropyl-1,3-dichlorodisiloxane, and 1,1,3,3-tetramethyl-1,3-diethoxydisiloxane.
[0042] Specific examples of crosslinkable silane compounds represented by general formula (2) include tris(trichlorosilylethyl)methylsilane, tris(triethoxysilylpropyl)amine, and tris(3-trimethoxysilylpropyl)isocyanurate.
[0043] Among these, 1,2-bis(trimethoxysilyl)ethane, 1,2-bis(triethoxysilyl)ethane, 1,6-bis(trimethoxysilyl)hexane, 1,8-bis(trimethoxysilyl)octane, 1,8-bis(triethoxysilyl)octane, 1,6-bis(trimethoxysilyl)-2,5-dimethylhexane, N,N'-bis[(3-trimethoxysilyl)propyl]ethylenediamine, 1,4-bis(trimethoxysilylethyl)benzene, 1,3-bis(trimethoxysilylpropyl)benzene, 4,4'-bis(triethoxysilyl)-1,1'-biphenyl, ris(triethoxysilylpropyl)amine, and tris-(trimethoxysilylpropyl)isocyanurate can be listed as particularly preferred crosslinkable silane compounds.
[0044] [Affinity silane compounds] Affinity silane compounds have alkyl groups that have high affinity for silicone resins. This makes it possible to obtain surface-treated aluminum nitride powder that has high dispersibility and water resistance with respect to silicone resins. Specific examples of affinity silane compounds having alkyl groups include methyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, cyclohexyltrimethoxysilane, cyclohexylmethyldimethoxysilane, n-octyltrimethoxysilane, n-octyltriethoxysilane, n-dodecyltrimexisilane, n-dodecyltriethoxysilane, trifluoropropyltrimethoxysilane, and trifluoropropylmethyldimethoxysilane.
[0045] Among these, ethyltrimethoxysilane, n-propyltriethoxysilane, n-hexyltriethoxysilane, n-octyltriethoxysilane, and n-dodecyltriethoxysilane can be listed as particularly preferred affinity silane compounds.
[0046] [Manufacturing method] The method for producing the surface-treated aluminum nitride powder of the present invention is not particularly limited, but one example is a method that includes the step of mixing the raw material aluminum nitride powder with a crosslinkable silane compound and an affinity silane compound, and then heating at 40°C or higher. This method will be described in detail below.
[0047] <Raw material: Aluminum nitride powder> In this specification, aluminum nitride powder before surface treatment is referred to as "raw material aluminum nitride powder." The raw material aluminum nitride powder can be any powder produced by conventionally known methods without particular limitation. Examples of methods for producing the raw material aluminum nitride powder include direct nitriding, reductive nitriding, and gas-phase synthesis. The particle size distribution of the raw material aluminum nitride powder is not particularly limited and can be appropriately determined considering the change in particle size due to the surface treatment of the target surface-treated aluminum nitride powder. For example, in the particle size distribution measured using a laser diffraction scattering particle size analyzer with water as the dispersion medium, the cumulative volume 50% particle size D50 is preferably in the range of 0.1 μm to 40 μm, and more preferably in the range of 0.3 to 25 μm. The raw material aluminum nitride powder may contain impurities such as alkaline earth elements and rare earth elements, either derived from the raw material or intentionally added during the synthesis process, up to a maximum of about 5 parts by mass. Furthermore, boron nitride may be contained as an anti-flocculation agent or an impurity derived from the manufacturing process, up to a maximum of about 5 parts by mass.
[0048] The aluminum nitride content in the raw material aluminum nitride powder is preferably 90% by mass or more, 95% by mass or more, and more preferably 99% by mass or more. In the method for producing surface-treated aluminum nitride powder of the present invention, it is preferable that the raw material aluminum nitride powder has an oxide layer formed on the particle surface with a thickness of 0.005% to 0.2% of the particle's D50, particularly 0.05% to 0.15%, in order to ensure more reliable bonding with the silane compound. The thickness of the oxide layer is measured by X-ray photoelectron spectroscopy-X-ray excited Auger electron spectroscopy. If the thickness of the oxide layer is less than 0.005% of the particle diameter, the amount of silane compound bonding tends to be insufficient, and if it exceeds 0.2%, there is a concern that it may hinder the thermal conductivity of the particles. This oxide layer may be formed by natural oxidation when the raw material aluminum nitride powder is stored, or it may be formed by an intentional oxidation treatment process. Furthermore, the oxidation treatment process may be carried out during the manufacturing process of the raw material aluminum nitride powder, or it may be carried out as a separate process after the manufacturing of the raw material aluminum nitride powder. For example, the raw material aluminum nitride powder obtained by the reduction nitriding method undergoes an oxidation treatment step in the manufacturing process to remove the carbon used in the reaction, so an aluminum oxide layer exists on the surface. An additional oxidation treatment step may be added to the aluminum nitride powder obtained by the reduction nitriding method. When the oxidation treatment step is added as a separate step, the preferred conditions are as follows: By heating the raw material aluminum nitride powder obtained by various methods in an oxidizing atmosphere, preferably at a temperature of 400 to 1,000°C, more preferably at 600 to 900°C, for a time of preferably 10 to 600 minutes, more preferably 30 to 300 minutes, an aluminum oxide layer can be formed on the surface of the raw material aluminum nitride particles. As the oxidizing atmosphere, for example, oxygen, air, water vapor, carbon dioxide, etc. can be used, but treatment in air, especially under atmospheric pressure, is preferred. On the other hand, if the oxidation treatment is performed at a high temperature exceeding 900°C for a long time, a thick aluminum oxide layer will be formed on the surface of the raw material aluminum nitride powder. Since this aluminum oxide layer has a different coefficient of thermal expansion than aluminum nitride, cracks may occur, potentially exposing the aluminum nitride surface.As a result, hydrolysis progresses from the exposed parts underwater, causing a decrease in water resistance. Therefore, it is best not to use overly harsh oxidation treatment conditions.
[0049] The shape of the primary particles of the raw material aluminum nitride powder in this invention is not particularly limited and can be any shape, such as irregular shape, spherical, polyhedral, columnar, whisker-shaped, or flat. Among these, for filler applications, a spherical shape is desirable because it has good viscosity characteristics and high reproducibility of thermal conductivity. Furthermore, a small particle aspect ratio is preferable. A suitable aspect ratio is 1 to 3.
[0050] <Surface treatment> The raw material aluminum nitride powder can be surface-treated by a method that includes the steps of adding and mixing a crosslinkable silane compound and an affinity silane compound to the raw material aluminum nitride powder, and then heating it at 40°C or higher. A heating temperature of 80°C or higher is preferable. The upper limit of the heating temperature should be less than the decomposition temperature of the crosslinkable silane compound and the affinity silane compound.
[0051] The total amount of the two types of silane compounds to be added is not limited, but is preferably 35 parts by mass or less, more preferably 20 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the raw material aluminum nitride powder. Furthermore, it is preferable to have 0.02 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 1 part by mass or more, per 100 parts by mass of the raw material aluminum nitride powder. By keeping the amount of silane compounds below the above upper limit, surface treatment can be easily performed without hindering heat conduction between particles. By keeping the amount of silane compounds above the above lower limit, it is easy to improve water resistance.
[0052] The amount of the crosslinkable silane compound is preferably 150 to 250 parts by mass, and more than 100 parts by mass, of the affinity silane compound, with a maximum of 100 parts by mass and a maximum of 300 parts by mass. By being above the lower limit, the spaces between adjacent affinity silane compounds on the aluminum nitride particles can be filled without excess or deficiency, resulting in high water resistance. By being below the upper limit, the effects of both the affinity silane compound and the crosslinkable silane compound can be achieved.
[0053] The method for mixing the raw material aluminum nitride powder with the crosslinkable silane compound and the affinity silane compound may be either a dry method or a wet method.
[0054] The dry process is carried out using no solvent or a small amount of solvent so that the raw material aluminum nitride powder remains in a powder state. It is preferable to ensure that the crosslinkable silane compound and the affinity silane compound are uniformly distributed on the surface of the aluminum nitride particles using a stirring device equipped with high stirring capacity and a mechanism for disintegrating agglomeration. The order in which the raw material aluminum nitride powder, crosslinkable silane compound, and affinity silane compound are mixed is not particularly limited, and they may be added to the raw material aluminum nitride powder after mixing. However, it is preferable to add the two types of silane compounds in stages (i.e., add and mix one silane compound, then add the other silane compound). In the case of combinations where there is a difference in the hydrophobicity of the affinity silane compound and the crosslinkable silane compound, the method of adding the two types of silane compounds in stages is particularly preferable. When adopting the staged addition method, the order in which the two types of silane compounds are added is not particularly limited, but it is preferable to add the crosslinkable silane compound first. By adding a crosslinkable silane compound beforehand, it becomes easier to further improve the affinity of the surface-treated aluminum nitride powder to the resin.
[0055] The method for adding the silane compound to the raw material aluminum nitride powder is not particularly limited, but it is preferable to add the silane compound by spraying or dropping it while stirring the raw material aluminum nitride powder. If the viscosity of the crosslinking silane compound or affinity silane compound is high and spraying or dropping is difficult, it may be diluted with a small amount of solvent. Any solvent capable of dissolving the crosslinking silane compound or affinity silane compound can be used without any problems, but a solvent with relatively high volatility and low viscosity is preferred, and alcohols and ketones are particularly desirable. The amount of diluting solvent used depends on the viscosity after dilution, but it is preferable to use about 0.5 to 50% by mass of the crosslinking silane compound and affinity silane compound.
[0056] For the dry mixing apparatus used for mixing after the addition of the silane compound, general mixing and stirring apparatuses can be used, such as planetary mixers, Henschel mixers, super mixers, V-type mixers, drum mixers, double-cone mixers, and rocking mixers. Among these, Henschel mixers, super mixers, and rocking mixers are more suitable due to their high stirring capacity. Furthermore, since powders tend to agglomerate during dry mixing, it is desirable that the mixing apparatus be equipped with a mechanism to break up agglomeration once it has formed, such as crushing blades or choppers. In addition, during the mixing operation, the powder may not only simply adhere, but depending on the stirring mechanism, the powder may be pressed against the walls of the mixing container, forming a thick layer of adhesion, in which case it becomes impossible to maintain the mixed state of the powder. For this reason, it is even better if the walls of the mixing container are equipped with anti-adhesion measures such as a fluororesin coating, a mechanism to remove adhering powder such as a knocker, or a scraping mechanism with specially designed stirring blades.
[0057] The wet method is a method of mixing raw material aluminum nitride powder and silane compounds using a solvent. Compared to the dry method, the wet method allows the silane compound to be uniformly distributed to all particles, resulting in less unevenness and easier production of powder with stable properties. In the wet method, for example, raw material aluminum nitride powder is dispersed in a solvent to which a silane compound has been added, the raw material aluminum nitride powder and silane compound are mixed, and then the solvent is removed.
[0058] The heating after adding and mixing the crosslinkable silane compound and affinity silane compound to the raw material aluminum nitride powder is performed to fix the silane compound to the surface of the aluminum nitride particles. If a solvent is used when adding or mixing the silane compounds, the solvent may be removed during this heating process. The heating temperature should be determined to be between 40°C and the decomposition temperature of the silane compounds, depending on the boiling points of the crosslinkable silane compound and affinity silane compound, for example, it can be between 40 and 150°C. The heating time is not particularly limited, but may be between 2 and 24 hours. Furthermore, the above heating may be performed under reduced pressure, and the pressure under reduced pressure should preferably be 10 hPa or less. Heating under reduced pressure makes it easier to remove excess silane compound, preventing the presence of an excess of free silane compound that is not fixed to the aluminum nitride powder, and also prevents powder aggregation due to the heat treatment.
[0059] <Post-surface treatment> The surface treatment may cause aggregation of the surface-treated aluminum nitride powder, which can impair powder properties and packing ability. In such cases, it is preferable to remove coarse particles by crushing or classification. Dry crushing is a good method for crushing. A relatively mild method is desirable so as not to crush most of the formed aggregates. In particular, if strong crushing that even crushes primary particles is performed with the appropriate equipment and conditions, the surface treatment of the surface-treated aluminum nitride particles may peel off, or the bare surface of the aluminum nitride may be exposed, worsening water resistance. Examples of dry crushing equipment include millstone-type grinders, pulverizers, cutter mills, hammer mills, and pin mills. Among these, millstone-type grinders are preferred because they can selectively crush large aggregates in a short time and produce less uneven crushing. The atmosphere for the crushing process is preferably in air or an inert gas. The humidity of the atmosphere should not be too high; specifically, it should be less than 70%, more preferably less than 55%.
[0060] As an alternative to crushing, classification can be used to remove coarse aggregated particles. Classification can be performed using either a dry or wet classification method. However, if high-precision classification is not required, the dry classification method, which eliminates the solvent removal step, is preferable. Dry classification methods include airflow classification and vibrating screens. The airflow classification method or apparatus should be appropriately selected to achieve a particle size distribution suitable for the filler. Airflow classification involves dispersing the powder in an airflow and separating it into fine and coarse powders based on gravity, inertia, and centrifugal force. In particular, the accuracy suitable for classifying particles of several micrometers can be achieved using a classification apparatus that utilizes inertia and centrifugal force. Methods that utilize inertial force include, for example, impactor-type systems that separate fine and coarse powders when bending granular materials, which have been propelled by the airflow, into a curve by creating a swirling airflow by installing guide vanes inside the device; semi-free-vortex centrifugal systems that classify particles by applying centrifugal force to them; and Coanda-type systems that utilize the Coanda effect. Classification devices that utilize inertial force include cascade impactors, viable impactors, aerofine classifiers, eddy classifiers, elbow jets, and hyperplexes. Methods that utilize centrifugal force separate fine and coarse powders using a swirling airflow, and include free-vortex and forced-vortex types of devices. Free-vortex devices include cyclones without guide vanes, multi-stage cyclones, turboplexes that use secondary air to promote the dissolution of agglomeration, dispersion separators with guide vanes to improve classification accuracy, microspins, and microcuts. Forced vortex classifiers are devices that improve classification accuracy by applying centrifugal force to particles using a rotating body inside the device and by creating another airflow inside the device. Examples include turboclassifiers and DonaSelec. The crushing and classification processes may be used in combination.
[0061] [water resistance] The surface-treated aluminum nitride powder of the present invention is stable even in water and exhibits excellent water resistance. For example, in a water resistance test in which 1 g of the surface-treated aluminum nitride powder and 50 g of deionized water are placed in a sealed container and heated at 85°C for 24 hours, it is preferable that the hydrolysis rate of the surface-treated aluminum nitride is 10% or less. Furthermore, in a water resistance test in which 1 g of the surface-treated aluminum nitride powder and 50 g of deionized water are placed in a sealed container and heated at 120°C for 24 hours, it is preferable that the hydrolysis rate of the surface-treated aluminum nitride is 10% or less. The hydrolysis rate of aluminum nitride in the hydrolysis test at 85°C or 120°C is more preferably 5% or less, and even more preferably less than 1%. The hydrolysis rate of the surface-treated aluminum nitride powder can be calculated from the amount of ammonium ions generated.
[0062] Furthermore, the surface-treated aluminum nitride powder of the present invention exhibits even higher water resistance when filled into silicone resin. That is, in addition to the high water resistance of the surface-treated aluminum nitride powder itself, the adhesion between the aluminum nitride particles and the silicone resin is high, so even if a silicone resin composition or its cured body filled with the surface-treated aluminum nitride powder is kept in high-temperature water for a long time, the penetration of water into the interior is suppressed. Therefore, hydrolysis of the filled surface-treated aluminum nitride is suppressed, resulting in high water resistance.
[0063] For example, in a water resistance test in which one of the following is performed: a mixture of silicone resins CY52-276A and CY52-276B (manufactured by Dow-Toray) (mass ratio 1:1) is mixed with surface-treated aluminum nitride powder to a packing density of 60 vol%, and these are kneaded vigorously in a mortar for 15 minutes to obtain a silicone resin composition, which is then heated and molded at 100°C for 3 hours to form a disc-shaped hardened body with a diameter of 10 mm and a thickness of 1.2 mm; and one of the disc-shaped hardened bodies and 50 g of ion-exchanged water are placed in a sealed container and heated at 120°C for 24 hours, it is preferable that the hydrolysis rate of the surface-treated aluminum nitride is 10% or less, more preferably 5% or less, and even more preferably less than 1%.
[0064] [Application] The surface-treated aluminum nitride powder of the present invention has high water resistance, high affinity with silicone resins, and excellent dispersibility, and is therefore preferably used as a filler for silicone resins, and particularly preferably as a heat dissipation filler for silicone resins.
[0065] [Silicone resin composition] A silicone resin composition containing a silicone resin and the surface-treated aluminum nitride powder of the present invention can be suitably used as a heat dissipation material. The silicone resin is not particularly limited, and known curable silicone resins, such as mixtures of addition-reaction type silicone resins and silicone-based crosslinking agents, can be used without limitation. Examples of addition-reaction type silicone resins include polyorganosiloxanes such as polydimethylsiloxane, which have alkenyl groups such as vinyl groups or hexenyl groups as functional groups in the molecule. Examples of silicone-based crosslinking agents include dimethylhydrogensiloxy group-terminated dimethylsiloxane-methylhydrogensiloxane copolymers, trimethylsiloxy group-terminated dimethylsiloxane-methylhydrogensiloxane copolymers, trimethylsiloxane group-terminated poly(methylhydrogensiloxane), poly(hydrogensilsesquioxane), and other polyorganosiloxanes having silicon atom-bonded hydrogen atoms. Furthermore, known platinum-based catalysts can be used without limitation as curing catalysts for curing the curable silicone resin. Examples include particulate platinum, particulate platinum supported on carbon powder, chloroplatinic acid, alcohol-modified chloroplatinic acid, olefin complexes of chloroplatinic acid, palladium, and rhodium catalysts. The silicone resin composition and its cured body, containing the silicone resin and the surface-treated aluminum nitride powder of the present invention, can be appropriately used as heat dissipation materials in applications requiring high thermal conductivity. This makes it possible to obtain a heat dissipation member containing the silicone resin composition or its cured body. Examples of such heat dissipation members include those for efficiently dissipating heat generated from semiconductor components mounted in home appliances, automobiles, and notebook personal computers. A specific example of such a heat dissipation material is, for example, thermal grease. These can be cited as examples. Since ionic impurities generated from these heat dissipation materials are likely to cause malfunctions in the device, the aforementioned silicone resin composition, which has high water resistance, is suitable for such applications. [Examples]
[0066] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these. The raw materials used and the conditions for measuring physical properties are described below.
[0067] [Raw material: Aluminum nitride powder] • I: Aluminum nitride powder prepared by reduction nitridation method (D50: 0.65 μm, Oxide layer thickness: 1 nm) • II: Aluminum nitride powder prepared by the reduction nitridation method (D50: 1.2 μm, Oxide layer thickness: 1 nm) • III: Aluminum nitride powder prepared by the reduction nitridation method (D50: 19 μm, Oxide layer thickness: 2 nm)
[0068] [Surface treatment agent] <Cross-linkable silane compounds> The following compounds were used. X1 to X4 are crosslinkable silane compounds similar to general formula (1), and X5 is a crosslinkable silane compound similar to general formula (2).
[0069] • X1: 1,2-Bis(triethoxysilyl)ethane
[0070] [ka]
[0071] • X2: 1,6-bis(trimethoxysilyl)hexane
[0072] [ka]
[0073] • X3: 1,8-Bis(trimethoxysilyl)octane
[0074] [ka]
[0075] • X4: 1,4-Bis(trimethoxysilylethyl)benzene
[0076] [ka]
[0077] • X5: Tris(triethoxysilylpropyl)amine
[0078] [ka]
[0079] • X6: Bis(trimethoxysilylundecyl) ether
[0080] [ka]
[0081] <Affinity-based silane compounds> • Y1: Ethyltrimethoxysilane • Y2: n-hexyltriethoxysilane • Y3:n-Octyltriethoxysilane • Y4:n-dodecyltriethoxysilane
[0082] [D50 measurement] Aluminum nitride powder was dispersed in a dispersion medium at a concentration of 0.2 mass%. The dispersion was then performed by ultrasonic irradiation at approximately 200W for 3 minutes. The particle size distribution of the resulting liquid was measured using a laser diffraction scattering particle size analyzer. For raw aluminum nitride powder, water (ion-exchanged water) was used as the dispersion medium, while for surface-treated aluminum nitride powder, ethanol was used. In the volume frequency distribution of particle size, the volume frequency was accumulated from the smallest particle size, and the particle size at which the cumulative value reached 50% was defined as D50.
[0083] [Measurement of hydrophobicity] In 200cc beakers, 100cc methanol aqueous solutions were prepared at concentrations in 1% by volume increments. 1g of surface treatment powder was added to each aqueous solution, and the solutions in the beakers were stirred with a magnetic stirrer for 5 minutes. The degree of hydrophobicity was defined as the volume percentage of methanol when 50% of the surface treatment powder was suspended in the solution.
[0084] [Measurement of carbon content] The carbon content of surface-treated aluminum nitride powder was measured using a carbon analyzer (EMIA-110, Horiba, Ltd.). The powder was burned in an oxygen stream at 1350°C until no more carbon dioxide gas was generated, and the carbon content of each powder was quantified from the amount of carbon dioxide generated.
[0085] [Measurement of specific surface area] The specific surface area was determined using the BET method (one-point nitrogen adsorption method) with a Shimadzu FlowSorb 2-2300 measuring device. For the measurement, 2 g of powder sample was used, which was pre-dried in a nitrogen gas flow at 100°C for 1 hour before being used for the measurement.
[0086] [Evaluation of viscosity when filled into silicone resin] Surface-treated aluminum nitride powder was added to silicone resin CY52-276A (manufactured by Dow-Toray) to a packing ratio of 40 vol%, and these were kneaded vigorously in a mortar for 15 minutes using shearing. The viscosity of the resulting mixture at 30°C was measured using a cone-plate viscometer (Brookfield BVNEXHBCBG, with a φ24 mm spindle and a 3° cone angle), and the shear rate was 2s. -1 The viscosity at that time was read. A lower viscosity of the mixture indicates a higher affinity between the surface-treated aluminum nitride powder and the silicone resin. The viscosity was judged as follows (A to F) based on the viscosity measured using surface-treated aluminum nitride powder that was surface-treated with the same affinity silane compound and the same raw material aluminum nitride powder. A: Viscosity 35% or more lower than the standard. B: 31-36% lower viscosity than standard. C: 26-30% lower viscosity than standard. D: 15-25% lower viscosity than standard. E: 1-15% lower viscosity than standard. F: Higher viscosity than or equivalent to the standard. Furthermore, the raw material aluminum nitride powder without surface treatment (Comparative Examples 1, 6, 11) and the surface-treated aluminum nitride powder treated only with crosslinkable silane compounds (Comparative Examples 19, 20) had higher viscosity than the surface-treated aluminum nitride powder treated only with affinity silane compounds (Comparative Examples 2-5, 7-10, 12-15), and were therefore given an F rating.
[0087] [Evaluation of powder water resistance] 1 g of aluminum nitride powder and 50 g of deionized water were placed in a sealed polytetrafluoroethylene container (PFA pressure-resistant jar, manufactured by Flon Industries Co., Ltd.) and allowed to stand at 85°C or 120°C for 24 hours. Ammonium ions eluted into the supernatant were quantified by ion chromatography (manufactured by Thermo Fisher Scientific), and the hydrolysis rate of aluminum nitride was calculated using formula (1). R AlN,h =C NH3 ×50×(MWAlN / MW NH3 ) × 10 -4 / W AlN (1) R AlN,h : Hydrolysis rate of aluminum nitride [%] C NH3 Concentration of ammonium ions dissolved in water [ppm] MW AlN : Molar mass of aluminum nitride [g / mol] MW NH3 : Molar mass of ammonia [g / mol] W AlN : Mass of aluminum nitride powder added to 50g of deionized water [g] The water resistance of the surface-treated aluminum nitride powder was evaluated according to the following criteria based on the hydrolysis rate of the aluminum nitride. ◎: Hydrolysis rate less than 1% ○: Hydrolysis rate 1~5% △: Hydrolysis rate 6~10% ×: Hydrolysis rate over 10%
[0088] [Evaluation of water resistance of cured silicone resin compositions] A mixture of silicone resins CY52-276A and CY52-276B (manufactured by Dow-Toray) in a mass ratio of 1:1 was mixed with surface-treated aluminum nitride powder to a packing density of 60 vol%, and these were kneaded vigorously in a mortar for 15 minutes. The resulting silicone resin composition was heated and molded at 100°C for 3 hours to obtain a cured body with a diameter of 10 mm and a thickness of 1.2 mm. One of the hardened bodies and 50g of deionized water were placed in a sealed polytetrafluoroethylene container (PFA pressure-resistant jar, manufactured by Flon Industries Co., Ltd.) and left to stand at 120°C. The dissolved substance in the supernatant liquid was The ammonium ions were quantified by ion chromatography (Thermo Fisher Scientific), and the hydrolysis rate of aluminum nitride was calculated using the above formula (1). AlN This was calculated from the weight of the cured material placed in 50g of deionized water and the amount of each component used in the manufacturing of the silicone resin composition. The water resistance of the cured product was evaluated according to the following criteria based on the hydrolysis rate calculated using formula (1). ◎: Hydrolysis rate less than 1% ○: Hydrolysis rate 1~5% △: Hydrolysis rate 6~10% ×: Hydrolysis rate over 10%
[0089] <Example 1> 150 g of raw material aluminum nitride powder I was mixed with 3.75 g of crosslinkable silane compound X1, stirred for 30 minutes with a fluororesin stirring blade, then 1.50 g of affinity silane compound Y4 was added dropwise and stirred for another 30 minutes. After that, the mixture was dried under reduced pressure at 100°C to obtain surface-treated aluminum nitride powder. The raw materials used are shown in Table 1, and the evaluation results of the obtained surface-treated aluminum nitride powder are shown in Table 2.
[0090] <Examples 2-21, Comparative Examples 16-18> Surface-treated aluminum nitride powder was obtained in the same manner as in Example 1, except that the type of raw material aluminum nitride powder, the type and amount of crosslinkable silane compound, and the type and amount of affinity silane compound were changed as shown in Tables 1 and 3. The raw materials used are shown in Tables 1 and 3, and the evaluation results of the obtained surface-treated aluminum nitride powder are shown in Tables 2 and 4.
[0091] <Comparative Examples 1, 6, 11> Comparative Example 1 evaluated raw material aluminum nitride powder I, Comparative Example 6 evaluated raw material aluminum nitride powder II, and Comparative Example 11 evaluated raw material aluminum nitride powder III. The evaluation results are shown in Table 4.
[0092] <Comparative Example 2> 150 g of raw material aluminum nitride powder I was mixed with 1.50 g of affinity silane compound, stirred for 30 minutes with a fluororesin stirring blade, and then dried under reduced pressure at 100°C to obtain surface-treated aluminum nitride powder. The raw materials used are shown in Table 3, and the evaluation results of the obtained surface-treated aluminum nitride powder are shown in Table 4.
[0093] <Comparative Examples 3-5, 7-10, 12-15> Surface-treated aluminum nitride powder was obtained in the same manner as in Comparative Example 2, except that the type of raw material aluminum nitride powder and the type of affinity silane compound were changed as shown in Table 3. The raw materials used and the evaluation results of the obtained surface-treated aluminum nitride powder are shown in Table 4.
[0094] <Comparative Example 19> 150 g of raw material aluminum nitride powder I was mixed with 1.50 g of a crosslinkable silane compound, stirred for 30 minutes with a fluororesin stirring blade, and then dried under reduced pressure at 100°C to obtain surface-treated aluminum nitride powder. The raw materials used are shown in Table 3, and the evaluation results of the obtained surface-treated aluminum nitride powder are shown in Table 4.
[0095] <Comparative Example 20> Surface-treated aluminum nitride powder was obtained in the same manner as in Comparative Example 19, except that the type of raw material aluminum nitride powder was changed as shown in Table 3. The raw materials used are shown in Table 3, and the evaluation results of the obtained surface-treated aluminum nitride powder are shown in Table 4.
[0096] [Table 1]
[0097] [Table 2]
[0098] Table 3
[0099] Table 4
Claims
1. Aluminum nitride powder surface-treated with at least two silane compounds, one of which is a crosslinkable silane compound represented by either of the following general formulas (1) or (2), and the other being an affinity silane compound having an alkyl group. A surface-treated aluminum nitride powder in which the crosslinkable silane compound is present in an amount of 100 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the affinity silane compound. 【Chemistry 1】 (In the above general formula (1), R 11 ~R 16 Each of these independently represents one of the following: a hydrocarbon chain, an alkoxy group, a hydroxyl group, a halogen atom, or a hydrogen atom, and each Si atom has at least one functional group capable of bonding to a hydroxyl group on the surface of the aluminum nitride particles. X represents a functional group with a single bond or a main chain connecting the Si atoms at both ends, with 1 to 14 atoms. 【Chemistry 2】 (In general formula (2), R 21 ~R 29 Each of these independently represents one of the following: a hydrocarbon chain, an alkoxy group, a hydroxyl group, a halogen atom, or a hydrogen atom. Each Si atom has at least one functional group capable of bonding to the hydroxyl group on the surface of the aluminum nitride particle. Y represents a functional group with 1 to 14 atoms in the main chain connecting the Si atoms at both ends.
2. The surface-treated aluminum nitride powder according to claim 1, wherein in a water resistance test in which 1 g of surface-treated aluminum nitride powder and 50 g of ion-exchanged water are placed in a sealed container and heated at 120°C for 24 hours, the hydrolysis rate of the surface-treated aluminum nitride is 10% or less.
3. The surface-treated aluminum nitride powder according to claim 1, wherein the cumulative volume 50% particle size (D50) measured by a laser diffraction scattering particle size analyzer, using ethanol as a dispersion medium, is in the range of 0.1 to 40 μm.
4. A filler for silicone resin comprising the surface-treated aluminum nitride powder described in any one of claims 1 to 3.
5. A silicone resin composition comprising a silicone resin and the filler described in claim 4.
6. A heat dissipation member comprising the silicone resin composition described in claim 5 or a cured product thereof.
7. A method for producing surface-treated aluminum nitride powder according to any one of claims 1 to 3, comprising the step of mixing raw material aluminum nitride powder, the crosslinkable silane compound, and the affinity silane compound, and then heating at 40°C or higher, wherein the amount of the crosslinkable silane compound is 100 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the affinity silane compound.
Citation Information
Patent Citations
Method for producing silicon-containing oxide-coated aluminum nitride particle and silicon-containing oxide-coated aluminum nitride particle
JP2020193141A
Hydrophobic aluminum nitride powder and production method therefor
WO2022131199A1